Studies on Lice Infesting Domestic Animals And Birds - Mohan M C (Department of Parasitology, College of Veterinary and Animal Sciences, 1979)
In a study on the lice of animals and birds in and around Trichur and their control, cattle was found to be infested with Haematopinus, quadripertuous and linognathu vituli. Buffaloes with haematopinus tuberoulatus, goats with linognathus africanus and damalinia cappre dogs with heterodoxus longitatsus. Elephatnts with haematomyzus elephantis and poultry with Menacanthus stramineus menopon gallinae, Goniodes gigas and Lipeurus caponis. Their incidence and intensity were maximum in winter and minimum in summer. Their morphology has been described in detail. For their control, Nuven, Malathion and sevin were tried and Nuven (0.05 percent) was found to be superior to the other two insecticides, with 100 percent efficacy.